Potentiel de productivite et efficacite technique du secteur agricole en Afrique - Nkamleu, G.B.; Nyemeck, J. (Wiley, 2006)
This study utilizes frontier metaproduction functions to analyze inter‐region agricultural productivity differences. Technical efficiency scores are examined through estimation of stochastic frontiers for 16 African countries divided into three different regions (West Africa, East and Southern Africa, and North Africa) from 1970 to 2001. The idea is to explore the differences in efficiency and technological gaps of agricultural sector. Apart of common traits that characterize African agricultural sector, countries exhibit national and regional specificities. These diversities are such that it is difficult to make valuable generalizations. It appears from the results that: in West Africa, the level of technology is relatively good, meaning that there is no problem of input constraints. By contrast, the efficiency with which inputs are used is very low. The situation is very different in the East and Southern Africa, with the level of technology relatively low and appreciable technical level. At least, the North Africa countries make a performing mixture between technology and efficiency.